Scalarane Sesterterpenoids Isolated from the Marine Sponge Hyrtios erectus and their Cytotoxicity - Huynh Nguyen Khanh Tran; Min Jin Kim; Yeon-Ju Lee (Marine Drugs, 2022)
Eighteen scalarane sesterterpenoids (1–18), including eight new derivatives (1–8), were isolated from the sponge Hyrtios erectus (family Thorectidae), the extract of which showed cytotoxicity against the HeLa and MCF-7 cell lines. Of the new derivatives, six compounds (1–6) were found to contain a γ-hydroxybutenolide moiety capable of reversible stereoinversion at the hydroxylated carbon center. Under the influence of other adjacent functional groups, each derivative exhibited a different stereochemical behavior, which was fully deduced by ROESY experiments. All the isolated compounds were examined for their cytotoxicity by MTS assay using staurosporine as a positive control (IC50 0.18 and 0.13 μΜ against HeLa and MCF-7 cells, respectively), and they were found to show weak growth inhibitory activities against HeLa and MCF-7 cells, with a minimal IC50 value of 20.0 μΜ. The compounds containing a γ-hydroxybutenolide moiety (1–3, 10, 12) showed cytotoxicity, with IC50 values ranging from 24.3 to 29.9 μΜ, and the most potent derivative was heteronemin (16). Although the cytotoxicities of isolated compounds were insufficient to discuss the structure–activity relationship, this research could contribute to expanding the structural diversity of scalaranes and understanding the stereochemical behavior of γ-hydroxybutenolides.